A Nationally Representative Survey of Faith and Work: Demographic Subgroup Differences around Calling and Conflict - Elaine Howard Ecklund; Denise Daniels; Daniel Bolger; Laura Johnson (Religions, 2020)
Research has increasingly highlighted the importance of business leaders allowing people to bring their whole selves to work. And religion is an important part of the whole self for many. However, we lack the large-scale national data needed to explore how Americans see the connections between religion and work. Here, from “Faith at Work: An Empirical Study”—a novel, nationally representative dataset—we explore the extent to which working Americans (N = 8767) see their work as a spiritual calling and/or experience work conflict because of their religious faith. We find that one fifth of workers identify their work as a spiritual calling. Our findings also suggest that experiences of religious conflict and discrimination are shaped not only by religious beliefs, but also social location. The initial results highlight future avenues for research and demonstrate the potential of the “Faith at Work” data to shed further light on how religion enters the workplace.